Gerakan Agama dan Budaya Komunitas Sekelik Sedulur dalam Mencegah Konflik Etnis di Lampung Tengah - M. Ali Syufa'at; Heri Cahyono; Ahmad Madkur (Ri'ayah: Jurnal Sosial dan Keagamaan, 2018)
This current paper discusses the movement Sekelik Sedulur community in building a culture of inter-ethnic harmony Lampung and Java as an attempt to Prevent ethnic conflict in Central Lampung. The core foundation of this community used a part of a cultural approach Harmony Among maintain ethnic, religious and community groups in Central Lampung. 'Sekelik' in Lampung means 'brother' and 'sedulur' in Javanese language means 'brother'. Community Sekelik Sedulur actively makes the discussion, friendship, and cultural acculturation activities in maintaining inter-ethnic relations. As Lampungnese were famous with the ethnic conflict, economic and social dialogue, it is Necessary to conduct forum as a form of concern for inter-ethnic harmony. Actually, the problems is there is no action blended multicultural entities. This study uses ethnographic approach. To answer the questions of this research, Utilization thinking of Koentjaraningrat Cultural is used as acculturation theory. Acculturation is a cultural fusion that occurs when a group of people with a certain culture are confronted with elements of a foreign culture so that different elements of foreign culture are gradually accepted and processed into their own culture without losing their own cultural identity